FLUORIDE CONCENTRATIONS IN COMMERCIALLY AVAILABLE PROCESSED BEVERAGES IN BRAZIL CONSUMED BY INFANTS - Sampaio, Caio [UNESP]; Botazzo Delbem, Alberto Carlos [UNESP]; Cabral de Assis Salama, Isabel Cristina [UNESP]; Cunha, Robson Frederico [UNESP]; Pessan, Juliano Pelim [UNESP] (Int Soc Fluoride Research, 2019)
Purpose: To determine fluoride concentrations of processed fruit juices (n=42) and ready-to-drink chocolate milks (n=9) commercially available in Aragatuba, Brazil, as well as estimating their contribution to the daily fluoride intake (DFI). Materials and methods: The beverages were purchased at supermarkets in Aragatuba, Brazil, and their fluoride contents were analyzed using an ion-specific electrode after overnight hexamethyldisiloxane (HMDS)-facilitated diffusion. The data were submitted to descriptive analysis. Results: The mean (SD) fluoride concentrations of the juices and chocolate milks were 0.17 (0.15) and 0.19 (0.21) mu g F/mL, respectively, with a range for all the beverages considered together of 0.02-0.62 mu g F/mL. The ranges of the values of the estimated DFI from these beverages in 2-year-old children, ranged from 0.0003-0.0091 F/kg body weight/day for a consumption of 200 mL/day and 0.0004-0.0136 mg F/kg body weight (bw)/day, for a consumption of 300 mL/day. Conclusion: Some of the products analyzed may be important contributors to the DFI and, therefore, can be regarded as potential risk factors for dental fluorosis, especially after considering the additional exposure from other sources.
Keywords: Fluorides; Fruit and vegetable juices; Milk; Dental fluorosis